Since
[tex]\dfrac{x^3}{x^2+2x+1}=\dfrac{x^3}{(x+1)^2}[/tex]
we can perform synthetic division twice, first for
[tex]\dfrac{x^3}{x+1}[/tex]
then dividing the result by [tex]x+1[/tex] again.
... || 1 0 0 0
-1 || -1 1 -1
================
... || 1 -1 1 -1
This translates to
[tex]\dfrac{x^3}{x+1}=x^2-x+1-\dfrac1{x+1}[/tex]
Now divide [tex]x^2-x+1[/tex] by [tex]x+1[/tex]. (Dividing the remainder term by [tex]x+1[/tex] can wait until the end.)
... || 1 -1 1
-1 || -1 2
=============
... || 1 -2 3
or equivalently,
[tex]\dfrac{x^2-x+1}{x+1}=x-2+\dfrac3{x+1}[/tex]
Taking everything together, we have
[tex]\dfrac{x^3}{x^2+2x+1}=\dfrac{x^2-x+1}{x+1}-\dfrac1{(x+1)^2}[/tex]
[tex]\dfrac{x^3}{x^2+2x+1}=x-2+\dfrac3{x+1}-\dfrac1{(x+1)^2}[/tex]
Combine the last two fractions:
[tex]\dfrac{x^3}{x^2+2x+1}=x-2+\dfrac{3(x+1)-1}{(x+1)^2}[/tex]
[tex]\dfrac{x^3}{x^2+2x+1}=x-2+\dfrac{3x+2}{(x+1)^2}[/tex]
which agrees with the solution we found in your other question.
(There's a variant of synthetic division that works with directly dividing a polynomial by another one of any degree, but it's basically just a condensed version of applying the algorithm for dividing a polynomial twice by a linear one, like we've done here.)